Partial Splenic Embolization Is a Safe and Effective Alternative in the Management of Portal Hypertension in Children. Issue 6 (June 2019) - Vittorio, Jennifer; Orellana, Katherine; Martinez, Mercedes; Ovchinsky, Nadia; Schlossberg, Peter; Griesemer, Adam; Lobritto, Steven
ABSTRACT: Objective: There are multiple approaches to manage the clinical complications of portal hypertension (PHTN) to treat/prevent spontaneous hemorrhage by mitigating thrombocytopenia. No single approach is ideal for all patients given the heterogeneity of this population. Our goal was to determine whether partial splenic embolization (PSE) was safe and effective in the pediatric population. Methods: This is a retrospective review of our single-center experience for all patients ages 0 to 21 who underwent PSE between January 2010 and August 2017. The embolized splenic volume targeted was 60% to 70%. Results: Twenty-six patients underwent PSE due to thrombocytopenia and/or recurrent variceal bleeding. Patients ranged in age from 18 months to 20 years (mean 13.1 years). The median platelet count before PSE was 53.0 (×10 9 /L). The platelet count improved after PSE with values >100, 000 in 21 patients (80.8%). Children with prior esophageal varices showed improvement after PSE with only 9 (34.6%) requiring further endoscopic therapy. After PSE, patients developed transient abdominal pain, distention, fever, and perisplenic fluid collections. Serious complications such as splenic abscess, splenic rupture, bleeding, pancreatic infarction, opportunistic infection, or death were not observed. One patient experienced thrombotic complications after PSE and was later diagnosed with myelodysplastic syndrome. Conclusions: PSE is a safe and effective alternative in the management of pediatric PHTN in select populations. PSE may be a favorable alternative to splenectomy and portal systemic shunting because it preserves functional spleen mass and avoids postprocedure accelerated liver disease or encephalopathy. Abstract : Supplemental Digital Content is available in the text